Analysis of Supporting and Inhibiting Factors in The Supervision of Importation of Dangerous Goods - Efendi, Yusuf; Wanto, Alfi Haris; Domai, Tjahjanulin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Directorate General of Customs and Excise has duties mandated by law, one of which is as a community protector. Community protection is the function of customs to protect the public against the entry of dangerous goods that are prohibited or restricted from importing by statutory provisions. In carrying out supervisory activities in carrying out the function of a community protector, it is necessary to analyze the supporting factors and inhibiting factors to achieve maximum tasks. The purpose of writing this paper is to find out the supporting factors and inhibiting factors in supporting the supervision activities carried out by customs in carrying out the community protector function in protecting the Indonesian people from the entry of dangerous goods. The author uses qualitative research methods with data collection techniques using interviews, observation and documentation. From the research conducted, it can be concluded that the supporting factors of supervision activities are the number of human resources, and the adequacy of supervision tools, all activities have used a computer service system. The inhibiting factors are not all people understand the provisions of customs, notification of imports of goods by self-assessment, intelligence analysis is still manual, limited human resources in intelligence analysts and potential safety threats to customs and excise officers.